Association of immune checkpoint inhibitors therapy with arterial thromboembolic events in cancer patients: A retrospective cohort study - Jie Zhu; Yue Chen; Yuanlong Zhang; Wei Wang; Yujue Wang; Zhuo Lu; Yulin Zhang; Haike Lei; Dairong Li; Bo Long; Haixia Liu (Cancer Medicine, 2023)
Abstract Background Immune checkpoint inhibitors (ICIs) have emerged as a standard treatment for various malignancies. However, research indicates blocking the immune checkpoint pathway may exacerbate atherosclerotic lesions. Objectives We aimed to investigate whether ICI therapy increases the risk of arterial thromboembolic events (ATEs). Methods A retrospective cohort study was conducted on patients with histologically confirmed cancer at our institution between 2018 and 2021, using the propensity score matching method. The primary endpoint was ATEs occurrence, comprising acute coronary syndrome, stroke/transient ischemic attack, and peripheral arterial thromboembolism. Subgroup analyses assessed whether the ICI treatment effect on ATEs varied over time by limiting the maximum follow‐up duration. Logistic regression analysis identified ATE risk factors in ICI‐treated patients. Results Overall, the ICI group (n = 2877) demonstrated an ATEs risk 2.01 times higher than the non‐ICI group (RR, 2.01 [95% CI (1.61–2.51)]; p < 0.001). Subgroup analysis revealed no significant increase in ATEs risk for ICI‐treated patients within 1 year (Limited to a max 9‐month follow‐up, p = 0.075). However, ATEs risk in the ICI group rose by 41% at 1 year (p = 0.010) and 97% at 4 years (p ≤ 0.001). Age, diabetes, hypertension, peripheral atherosclerosis, atrial fibrillation, chronic ischemic heart disease, distant cancer metastasis, and ICI treatment cycles contributed to ATEs risk elevation in ICI‐treated patients. Conclusion ICI‐treated patients may exhibit a higher risk of ATEs, especially after 1 year of treatment.